The impact of high and growing government debt on economic growth: an empirical investigation for the euro area - Cristina Checherita-Westphal; Philipp Rother (European Central Bank (ECB), 2010)
This paper investigates the average impact of government debt on per-capita GDP growth in twelve euro area countries over a period of about 40 years starting in 1970. It finds a non-linear impact of debt on growth with a turning point—beyond which the government debt-to-GDP ratio has a deleterious impact on long-term growth—at about 90-100% of GDP. Confidence intervals for the debt turning point suggest that the negative growth effect of high debt may start already from levels of around 70-80% of GDP, which calls for even more prudent indebtedness policies. At the same time, there is evidence that the annual change of the public debt ratio and the budget deficit-to-GDP ratio are negatively and linearly associated with per-capita GDP growth. The channels through which government debt (level or change) is found to have an impact on the economic growth rate are: (i) private saving; (ii) public investment; (iii) total factor productivity (TFP) and (iv) sovereign long-term nominal and real interest rates. From a policy perspective, the results provide additional arguments for debt reduction to support longer-term economic growth prospects.
Keywords: H63; O40; E62; E43; 330; Economic Growth; Fiscal Policy; public debt; sovereign long-term interest rates; Öffentliche Schulden; Wirtschaftswachstum; Finanzpolitik; Zinsstruktur; EU-Staaten